Uma discussão sobre documento audiovisual enquanto patrimônio arquivístico cultural no Brasil - Da Silva, Luiz Antonio Santana [UNESP]; De Carvalho Madio, Telma Campanha [UNESP] (My University, 2012)
The origin of the concept of cultural heritage and its definition and applicability to the Brazilian scenery is analyzed, with a focus on audiovisual archives.
A discussion on audiovisual documents as cultural and archival heritage in Brazil
Keywords: Archives; Audiovisual documents; Cultural heritage